Zasnova športne infrastrukture v prostoru - Leskovec, Boris (Urbani izziv, 1998)
Harmonious development of sports deals with development of sports centres, buildings and training grounds in the built environment. Their basic objectives is to provide to needs of professional and top quality sports, sports recreation and sports education in space. The methodological basis for establishing a spatial sports scheme was the Steinitz-Rogers model of planning sports-recreation centres, buildings and training grounds. One of the results of the scheme is a cartographically and digitally supported data base, that can be complemented.
Keywords: architecture; arhitektura; infrastructure; infrastruktura; planiranje; prostorsko planiranje; spatial planning; športni objekti